2017
DOI: 10.1007/s11999-016-4931-z
|View full text |Cite
|
Sign up to set email alerts
|

No Difference in Early Analgesia Between Liposomal Bupivacaine Injection and Intrathecal Morphine After TKA

Abstract: Background Opioid analgesics have been a standard modality for postoperative pain management after total knee arthroplasty (TKA) but are also associated with increased risk of nausea, pruritus, vomiting, respiratory depression, prolonged ileus, and cognitive dysfunction.There is still a need for a method of anesthesia that can deliver effective long-term postoperative pain relief without incurring the high cost and health burden of opioids and nerve blocks. Questions/purposes (1) Is liposomal bupivacaine-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 87 publications
(92 reference statements)
1
45
1
3
Order By: Relevance
“…2). [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Four studies 7,13,15,18 compared other groups in addition to liposomal bupivacaine and traditional PAI, so we selected only the data related to liposomal bupivacaine and traditional PAI for analysis. Finally, nine RCTs and seven nRCTs were included in our review (►Table 1).…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…2). [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Four studies 7,13,15,18 compared other groups in addition to liposomal bupivacaine and traditional PAI, so we selected only the data related to liposomal bupivacaine and traditional PAI for analysis. Finally, nine RCTs and seven nRCTs were included in our review (►Table 1).…”
Section: Study Selectionmentioning
confidence: 99%
“…There were 924 liposomal bupivacaine cases and 1,293 traditional PAI cases in the 16 included studies. In most studies, the mean age was between 60 and 70 years old, and was 69 years in the oldest group 15 and 48 years in the youngest group. 10 All studies reported the gender of the patients.…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…The use of LB in Total Knee Arthroplasty (TKA) has been heavily investigated with studies demonstrating varying results. A few studies have demonstrated an efficacy of LB close to that of regional femoral blockade and others have shown that it can significantly decrease postoperative narcotic use, length of stay, and postoperative Visual Analog Scale (VAS) scores [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Although many studies have shown the potential advantages of its use, many other studies have exhibited no benefit of its use in TKA The Efficacy of Liposomal Bupivacaine in Lumbar Spine Surgery…”
Section: Introductionmentioning
confidence: 99%